Pengaruh Persepsi Akan Reward terhadap Motivasi Belajar Siswa SDN Simpang Empat 3 - Gamilina, Pranciska; Noor, Muhammad (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2025)
This study is motivated by the limited specific empirical studies regarding how students' perceptions of concrete reward provision affect various dimensions of learning motivation in the learning environment, especially at the elementary school level, which is a crucial foundation of education. Learning motivation has a significant impact on the success of the learning process. The purpose of this study is to examine the effect of perceptions of reward provision on students' learning motivation at SDN Simpang Empat 3. The method used is quantitative with a correlational design, employing simple linear regression analysis, with a sample of 31 students from grades V and VI selected through total sampling techniques. Data were collected through a questionnaire and analyzed using normality tests, linearity tests, and simple linear regression analysis. The results indicate that there is a positive and significant effect of reward perception on students' learning motivation, with a significance value of reward perception of 0.005 (< 0.05) and a coefficient of determination (R Square) of 0.245, meaning that reward perception contributes 24.5% to enhancing students' learning motivation. These findings align with the purpose of the study and reinforce reinforcement theory. The main conclusion of this study is that students' perceptions of rewards empirically affect learning motivation at the elementary school level. The implications of this research include theoretical aspects, such as enriching the literature on the dynamics of rewards and motivation in the context of elementary schools, as well as practical aspects, namely recommendations for educators and school stakeholders to consider comprehensive strategies that include various other factors affecting learning motivation. This study also opens opportunities for further research on other factors (75.5%) that influence students' learning motivation.